Telematics system for the intelligent transport and distribution of medicines. Issue 1 (1st March 2013) - Garcia Zuazola, Ignacio Julio; Moreno, Asier; Landaluce, Hugo; Angulo, Ignacio; Perallos, Asier; Hernández‐Jayo, Unai; Sainz, Nekane; Ziai, Mohamed A.; Batchelor, John C.; Elmirghani, J.M.H.
Abstract : A growing demand for well‐defined telematics systems in the intelligent transport distribution of pharmaceutical drugs is envisaged driven by legislative demands to enable the safe handling of medicines in automotive distributions. The provision is accomplished by providing virtual intelligence to vehicles designated for this form of smart freight transportation. The system provides anytime/anywhere assets tracking while on the move, from departure to destination, supporting reliable courier operation at low labour. The tracking and tracing system provides the vehicle with sufficient intelligence to: be located remotely, track and trace assets and provide incidence reports. The authors' architecture is intended to automatically broadcast adaptive logistic‐distribution‐plans between a central office and a vehicle. The proposed system represents an inexpensive and non‐intrusive solution that exploits advanced technologies such as smart environment sensing, radio frequency identification, Wireless Fidelity (WiFi) and global positioning system, to support modern industrial needs. The authors describe and discuss the motivation and the beneﬁts of using the system, including new hardware and software developments.